Closed-cycle management strategy for hospital infection prevention and control in the designated dental hospital for the Winter (Paralympic) Olympic Games to receive emergency dental emergency patients (冬(残)奥会指定口腔医院接诊涉奥口腔急诊患者的院感防控闭环管理策略) - AN Na (安娜); CHEN Qiujing (陈秋静); HU Feng (呼峰); XUE Liang (薛亮); MA Yong (马泳); XIA Dengsheng (夏登胜) (中西医结合护理, 2022)
The 2022 Beijing Winter (Paralympic) Olympics ［abbreviated as the Winter (Paralympic) Olympics］ had been held. Our hospital was the designated oral medical institution during the Winter (Paralympic) Olympics, and nosocomial infection control was a formidable challenge for medical staff. In this paper, referring to the infection prevention and control standards of the emergency department of the dental specialist hospital, combined with the situation of the COVID-19, a dedicated isolation channel and independent consultation room for Olympic-related patients and medical staff were set up; Medical staff (the training pass rate was 100%)strictly took personal protection before and after treatment and during treatment, and the diagnosis and treatment areas (surfaces of items, reused medical equipment, and so on) were strictly disinfected, and a total of 38 patients were admitted. For Olympic-related patients, the patient satisfaction rate was 100%; 304 environmental points were collected, all were negative, and no nosocomial infection occurred. This article elaborates the specific measures of closed-loop management of hospital infection prevention and control in detail. (2022年北京冬季奥林匹克运动会(简称冬奥会)和冬季残疾人奥林匹克运动会(简称冬残奥会)举办期间, 本院为冬(残)奥期间指定口腔医疗机构, 在冬(残)奥期间接诊涉奥患者, 医院感染控制是一项艰巨的挑战。医院参考口腔专科医院急诊科感染防控标准, 结合新型冠状病毒肺炎疫情防控情况, 设置涉奥患者和医护人员专用隔离通道和独立诊室; 共有6名医护人员(分3组, 每组医生护士各1名)进入闭环, 分批值岗, 培训合格率100. 00%; 医护人员在治疗前后、治疗时均严格做好个人防护, 诊疗区域(物品表面、复用医疗器械等)严格消毒, 共接诊38名涉奥患者, 患者满意率100. 00%; 采集304个环境点位, 均为阴性, 无院内感染发生。本文就院感防控闭环管理的具体措施进行详细阐述。)